Comparative Effect of Cattle Rumen Digesta and Poultry Droppings in Bioremediation of Spent Engine Oil-Contaminated Soil - Nkereuwem, Michael; Adeleye, Adeniyi; Ijah, Christiana; Tersoo , Paul; Lawan , Usman; Amoo , Afeez; Auwalu , Abubakar (Indonesian Journal of Green Chemistry, 2025)
The study was conducted to compare the bioremediation potentials of two organic wastes (Cattle Rumen Digesta-CRD and Poultry Droppings-PD) in SEO contaminated soil in Dutse, Jigawa State. About 3 kg of soil was contaminated with SEO at 3 levels (0, 100 and 150 mL/pot). After 2 weeks of contamination, CRD and PD were added at 0 and 20 g/pot and thoroughly mixed. It was a 2 x 2 x 3 factorial experiment in completely randomized design replicated thrice. The incubation study lasted for 12 weeks. Data were collected on the Total Petroleum Hydrocarbon (TPH), bacterial and fungal counts of the SEO contaminated soil and analyzed using ANOVA at p<0.05. Results obtained shows that CRD and PD application at 20 g/pot yielded significantly (p<0.05) lower residual TPH contents (375 mg/kg and 704 mg/kg) of the SEO-impacted soil compared to the control. However, the residual TPH content of the contaminated soil obtained from the combination of 20 g/pot CRD with 100 mL/pot SEO was significantly (p<0.05) lower (252 mg/kg) compared to the residual TPH content (641 mg/kg) obtained from the combination of 20 g/pot PD and 100 mL/pot SEO. Interaction of 20 g/pot CRD with 100 mL/pot SEO had higher bacterial and fungal counts (21.03 and 16.80 CFU/g soil) compared to combination of 20 g/pot PD with 100 mL/pot SEO (16.48 and 15.80 CFU/ g soil). Thus, it is concluded that cattle rumen digesta has a higher biodegradation capacity than poultry droppings and was more effective in the bioremediation of SEO contaminated soil.